Postcolonialism and the Study of Anti-Semitism. Issue 4 (4th October 2018) - Cheyette, Bryan
Abstract: In recent years Hannah Arendt's The Origins of Totalitarianism (1951) has become a common point of reference for those within postcolonial studies—such as Paul Gilroy, Aamir Mufti, and Michael Rothberg—who wish to explore the historical intersections between racism, fascism, colonialism, and anti-Semitism. "Postcolonialism and the Study of Anti-Semitism" relates Arendt's comparative thinking to other anticolonial theorists and camp survivors at the end of the Second World War—most prominently, Jean Améry, Aimé Césaire, Frantz Fanon, Albert Memmi, Primo Levi, and Jean-Paul Sartre—who all made connections between the history of genocide in Europe and European colonialism. The article then compares this strand of comparative thought with postcolonial theorists of the 1970s and 1980s who, contra Arendt, divide the histories of fascism and colonialism into separate spheres. It also contrasts postcolonial theory with postcolonial literature by exploring the intertwined histories in the fiction of V. S. Naipaul, Salman Rushdie, and Caryl Phillips. Said's late turn to Jewish exilic thinkers such as Theodor Adorno, Erich Auerbach, and Sigmund Freud is also related to this Arendtian comparative project. The main aim of the article is to promote a more open-minded sense of historical connectedness with regard to the histories of racism, fascism, colonialism, and anti-Semitism.